Zakat and Poverty Alleviation Among People With Disabilities In Gombe State Nigeria: A Critical Analysis (UIN Sunan Kudus, 2022)
Zakat is an Islamic financial instrument that plays a variety of roles in human life, including providing assistance to vulnerable members of society, with particular reference to people with disabilities. This paper examines the institution of Zakat as a tool for alleviating poverty in Nigeria in general and Gombe state in particular, as well as the key roles of Zakat institutions and their problematic operation in the study area. The qualitative method for the study was developed through a literature review and interviews with relevant individuals. The study's findings revealed that the poverty rate of individuals with disabilities is higher than that of any other sub-group of individuals without a disability; thus, societal attitudes toward people with disabilities must be reconsidered immediately. The use of zakat income is a relevant tool for strengthening the skills of vulnerable people, part of which is disabled people. The implications of this study serve as a basis for making recommendations for expanding the scope of distribution of Zakat properties by including consumable properties and cash, as well as textile materials and entrepreneurial packages for the most talented disabled individuals to develop and finance the businesses they have in order to develop poverty alleviation programs in the state.